Study of Rheological Property and Flow Behavior for Nanoparticles Enhanced VES System in Porous Media - Liu, Zhaoxia; Wang, Qiang; Gao, Ming; Luo, Wenli; Cai, Hongyan (Frontiers in Energy Research, 2021)
Polymer flooding represents one of the most efficient processes to enhance oil recovery, and partially hydrolyzed polyacrylamide (HPAM) is a widely used oil-displacement agent, but its poor salt tolerance, and mechanical degradation impeded its use. In this work, a novel hybrid samples (viscoelastic surfactant and SiO2 nanoparticle) was used to overcome the deficiencies of HPAM. The rheological behaviors of VES/nanoparticles hybrid and flow behavior in porous media were examined. It was found that SiO2 nanoparticles exhibited viscosifying action and improved the oil tolerance. In addition, core flooding tests showed that the oil recovery factors of the VES solution without nanoparticles were poor, which may be attributed to the collapse of the micelles upon contacting residual oil, and the disassembled micelles. On the contrary, 9.68% of oil recovery factor was achieved from the hybrid sample in the high permeability core flooding test for the VES sample with nanoparticles which is relatively stable with oil, thus effectively improving water-to-oil mobility ratio to make more oil produced.